The Business Model Development of PT Cahaya Majumedika - Wardhana, Boma; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2015)
Abstract.Medical Equipment Industry potential is very attractive currently. With support by Indonesia Government will increasing the growth of this industry. Running a medical equipment industry is require professional management and competencies to move forwards the growth phase. With ten years experience in this business, PT Cahaya Majumedika still only capturing West-Java and Bangka-Belitung markets area while the younger competitor has fast growth compare to them. It is important for PT Cahaya Majumedika to understanding their business model in order to keep sustain in this industry. This research is to analyze PT Cahaya Majumedika business in West-Java and Bangka-Belitung and the analysis result will become cornerstone and expected to lead for an appropriate business model. This research used related theories to business model and strategic management for literature review and qualitative research methodologies to collect primary data. Field Observation and in-depth interview with relevant experts with commissioner and sales marketing manager were conducted to understand intangibles data. Based on root cause analysis and questions at in-depth interviews, slow growth of PT Cahaya Majumedika business is caused by lack of business model understanding. From Generic Competitive Strategy, PT Cahaya Majumedika should keep focus on differentiation strategy by providing premium products and making innovation of their services and performance. With Business Diamond Strategy, PT Cahaya Majumedika should develop their products with adding disposable products to have continuesly order from customer. Broadening its service innovation, Build strong brand image & awareness, and Broadening channels and geographics arenas in Indonesia are also solutions that given from using Business Diamond Strategy. While on Business Model Canvas used as a tools and described more detail for companyâ€™s new innovative strategy.Keywords: Business Model, Medical equipment, Supplier, Business Model CanvasÂ Â